Proposed the new design new air and deionized water piping system at FKKSA"s laboratory - Muhammad Haidar, Hussien (2010)
The air and deionized water piping recently is drawn 3D by using Plant Design Management System (PDMS). The PDMS is used worldwide not only for piping design but it can design as big as plant, factory and offshore platform. The main objective for this research is to design new air and deionized water piping system for improving recent piping system to make sure it can support the increasing demand of deionized water and air due to new equipments installation. The faculty of chemical and natural resources (FKKSA) laboratory is used as model for the drawing. Pressure drop is the main calculation for piping. It will determine either fluid will flow smoothly and reach the next point of the pipe. For the calculation, initial pressure of air is 125 psi and deionized water is 18 psi. The pressure drop percentage must not exceed 30 percent or otherwise the fluid cannot reach the next point of pipe. As the result, the fluid will flow to the final point of pipe because the pressure drop percentage is not exceeding 30 percent. Piping materials also crucial for piping and it is depends on the type of fluid. Deionized water piping use cross linked polyethylene (PEX) because of it corrode resistant, resist with high temperature and will use only few fittings but air use smart pipe that made of 6035-T5 calibrated alloy aluminium and coated with blue powder that is non flammable and 100 percent recyclable. In conclusion, the new air and deionized water piping system can support the demand of additional equipments in FKKSAâs laboratory.